Surveillance of Food- and Smear-Transmitted Pathogens in European Soldiers with Diarrhea on Deployment in the Tropics: Experience from the European Union Training Mission (EUTM) Mali. (11th October 2015) - Frickmann, Hagen; Warnke, Philipp; Frey, Claudia; Schmidt, Salvatore; Janke, Christian; Erkens, Kay; Schotte, Ulrich; Köller, Thomas; Maaßen, Winfried; Podbielski, Andreas; Binder, Alfred; Hinz, Rebecca; et al.
Abstract : Introduction . Since 2013, European soldiers have been deployed on the European Union Training Mission (EUTM) in Mali. From the beginning, diarrhea has been among the most "urgent" concerns. Diarrhea surveillance based on deployable real-time PCR equipment was conducted between December 2013 and August 2014. Material and Methods . In total, 53 stool samples were obtained from 51 soldiers with acute diarrhea. Multiplex PCR panels comprised enteroinvasive bacteria, diarrhea-associated Escherichia coli (EPEC, ETEC, EAEC, and EIEC), enteropathogenic viruses, and protozoa. Noroviruses were characterized by sequencing. Cultural screening for Enterobacteriaceae with extended-spectrum beta-lactamases (ESBL) with subsequent repetitive sequence-based PCR (rep-PCR) typing was performed. Clinical information was assessed. Results . Positive PCR results for diarrhea-associated pathogens were detected in 43/53 samples, comprising EPEC (n = 21 ), ETEC (n = 19 ), EAEC (n = 15 ), Norovirus (n = 10 ), Shigella spp./EIEC (n = 6 ), Cryptosporidium parvum (n = 3 ), Giardia duodenalis (n = 2 ), Salmonella spp. (n = 1 ), Astrovirus (n = 1 ), Rotavirus (n = 1 ), and Sapovirus (n = 1 ). ESBL-positive Enterobacteriaceae were grown from 13 out of 48 samples. Simultaneous infections with several enteropathogenic agents were observed in 23 instances. Symptoms were mild to moderate. There were hints of autochthonous transmission. Conclusions . Multiplex real-time PCR proved to be suitable for diarrhea surveillance on deployment. Etiological attribution is challenging in cases of detection of multiple pathogens.